2021
DOI: 10.1530/eje-21-0162
|View full text |Cite
|
Sign up to set email alerts
|

ENDOCRINE TUMOURS: Thyrotropin-secreting pituitary adenoma: a structured review of 535 adult cases

Abstract: Background and Aims: Thyrotropin-stimulating pituitary adenoma (TSHoma) are a rare entity, occurring in 1 per million people. We performed a systematic review of 535 adult cases summarizing the clinical, biochemical, hormonal and radiological characteristics of TSHoma. Furthermore, we discuss the current guidelines for diagnosis and treatment. Methods A structured research was conducted using Pubmed with the following MeSH terms: “thyrotropin secreting pituitary adenoma” OR “TSHoma” OR “thyrotropinoma”. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
1
15

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(66 citation statements)
references
References 32 publications
5
40
1
15
Order By: Relevance
“…Arrhythmia and valvular diseases were seen in more than 30% of the TSH-oma cases at our center. Recently, a meta-analysis revealed that atrial fibrillation or heart failure happened in 11.1% of 535 adult TSH-oma cases ( 22 ). Another research found that TSH-oma can significantly induce left atrial enlargement and subclinical atrial fibrillation since excess thyroid hormones can increase the arrhythmogenic activity of the pulmonary veins, and increase the hemodynamic load ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Arrhythmia and valvular diseases were seen in more than 30% of the TSH-oma cases at our center. Recently, a meta-analysis revealed that atrial fibrillation or heart failure happened in 11.1% of 535 adult TSH-oma cases ( 22 ). Another research found that TSH-oma can significantly induce left atrial enlargement and subclinical atrial fibrillation since excess thyroid hormones can increase the arrhythmogenic activity of the pulmonary veins, and increase the hemodynamic load ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…They represent a rare cause of central hyperthyroidism characterized by normal or inappropriately high Thyroidstimulating hormone (TSH) concentrations in the presence of elevated free-thyroid hormones (fT3 and fT4) [111]. The treatment of choice for TSHomas is surgery, with a complete resection of the tumor achieved in two-thirds of patients [112]. The rather disappointing results of surgery (especially for the frequently detected macroadenomas) indicate that additional treatment, such as radiotherapy or medical treatment, may be necessary.…”
Section: Tsh-secreting Pt (Tshomas)mentioning
confidence: 99%
“…[7]. К настоящему времени в литературе опубликовано около 535 случаев ТТГ-секретирующих аденом гипофиза [8]. Благодаря использованию в клинической практике высокочувствительных иммунометрических методов определения ТТГ, а также широкой доступности МРТ и КТ, частота выявления тиреотропином постепенно увеличивается [9].…”
Section: эпидемиологические аспекты ттг-секретирующих аденом гипофизаunclassified
“…По данным Р. Beck-Peccoz и соавт., около 25% тиреотропином обладают смешанной секрецией, чаще встречается сочетание гиперсекреции ТТГ и соматотропного гормона (СТГ) (18,3%), реже -ТТГ и пролактина (9,7%) и крайне редко -ТТГ и гонадотропных гормонов (1,7%) [12]. При этом в других исследованиях косекреция ТТГ и других гормонов гипофиза наблюдалась примерно в 40% случаев, в 55% которых выявлена коэкспрессия с СТГ, а в 40% -коэкспресия с пролактином [8,13]. Следует отметить, что положительная иммуноэкспрессия, выявленная по данным иммуногистохимического исследования, не всегда сопровождается повышением концентрации гормонов в крови.…”
Section: этиология и патогенез тиреотропиномunclassified